Vagus Nerve Stimulation for Refractory Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The efficacy of vagus nerve stimulation (VNS) was evaluated in 24 patients, aged 4 to 40 years (median 18 years), at the New York Presbyterian Hospital-Cornell Medical Center, NY; Mercy Children's Hospital, Kansas City; and University of California at San Diego.